MANAJEMEN LISTRIK MENGGUNAKAN VOICE RECOGNIZE DENGAN PENDEKATAN MACHINE LEARNING - Banyu Ontoseno (2023)
In today's modern era, technology is very ordinary for everyone in any circle. This is because technology can help make human work easier, time-consuming and labor-intensive work can be replaced by technology. Although it seems that technology seizes human employment, we must realize that over time, humans will experience aging which has a direct effect on human energy and mind, so that the work done becomes less efficient and effective, for example, technicians who still operate electrical goods in a building manually or have to directly interact with the object closely. Even though it seems trivial, imagine if the building has floors with a level of more than 10. The technology developed by researchers can be useful for managing this from the ground floor, so that technicians no longer need to go up and down the floor level to do the electricity management. Researchers use a microcontroller which will be the basis for regulating these electrical objects, as well as voice recognition with an artificial intelligence approach to make it easier for technicians to carry out electrical management, as well as verify voice ownership so that it is not managed by just any party, except the one that have permission for it. Researchers hope that the developed tools will be useful as well as useful for technicians working in high-rise buildings.